2020
DOI: 10.1016/j.pmedr.2020.101162
|View full text |Cite
|
Sign up to set email alerts
|

Trends and sociodemographic disparities in sugary drink consumption among adults in New York City, 2009–2017

Abstract: Highlights We studied the trends in sugary drink consumption among adults in New York City. Sugary drink consumption decreased from 2009 to 2014 but plateaued from 2014 to 2017. Sugary drink consumption remained high among young adults, Hispanics, and Blacks. Targeted interventions are needed to reduce disparities in sugary drink consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A few recent trends bolster the flattened SSB purchase trend we identified. Jiang et al (2020) identified a similarly flat 2014-2017 pattern in SSB consumption among adults in New York City [45], and industry sales of sugary drink calories per person per day have demonstrated a plateaued trend since 2013 [19,46].…”
Section: Discussionmentioning
confidence: 99%
“…A few recent trends bolster the flattened SSB purchase trend we identified. Jiang et al (2020) identified a similarly flat 2014-2017 pattern in SSB consumption among adults in New York City [45], and industry sales of sugary drink calories per person per day have demonstrated a plateaued trend since 2013 [19,46].…”
Section: Discussionmentioning
confidence: 99%
“…In a typical American diet, SSBs are the number one source of added sugars (Huth, Fulgoni, Keast, Park, & Auestad, 2013), and are associated with increased rates of diabetes, osteoporosis, liver disease, heart disease, stroke and cancer (Chazelas et al, 2019; Kim & Je, 2016; Micha et al, 2017; Singh et al, 2015). In the United States, SSBs are disproportionately marketed to, and consumed by, Black and Latino youth compared to American youth at large (Herrera & Pasch, 2018; Isselmann DiSantis et al, 2017; Jiang et al, 2020; Park, Xu, Town, & Blanck, 2016; Ramirez, Gallion, & Adeigbe, 2013). In New York City, SSBs are disproportionately marketed to communities of color through targeted subway station and street-level billboard advertising and retail product placement (Dowling, Roberts, Adjoian, Farley, & Dannefer, 2020; Lucan, Maroko, Sanon, & Schechter, 2017).…”
Section: Introductionmentioning
confidence: 99%